Comprehensive Physiology 2011
DOI: 10.1002/cphy.c100038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the Nucleus

Abstract: The nucleus is the distinguishing feature of eukaryotic cells. Until recently, it was often considered simply as a unique compartment containing the genetic information of the cell and associated machinery, without much attention to its structure and mechanical properties. This article provides compelling examples that illustrate how specific nuclear structures are associated with important cellular functions, and how defects in nuclear mechanics can cause a multitude of human diseases. During differentiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 210 publications
(384 reference statements)
7
138
0
Order By: Relevance
“…The nucleus, however, is mechanically connected to the cytoplasm and deforms as the cell deforms, supporting the observation that transcriptional activity can be affected rapidly 140 . Recent studies have identified a class of nuclear membrane proteins called lamins that are mechanosensitive and involved in a number of clinical conditions, including progeria and cancer 141 . Recently, we stretched mouse valve leaflets ex vivo and followed local cell and matrix fiber deformations in combination with global tissue stretch 142 .…”
Section: Molecular Mediators Of Valve Mechanobiologysupporting
confidence: 56%
“…The nucleus, however, is mechanically connected to the cytoplasm and deforms as the cell deforms, supporting the observation that transcriptional activity can be affected rapidly 140 . Recent studies have identified a class of nuclear membrane proteins called lamins that are mechanosensitive and involved in a number of clinical conditions, including progeria and cancer 141 . Recently, we stretched mouse valve leaflets ex vivo and followed local cell and matrix fiber deformations in combination with global tissue stretch 142 .…”
Section: Molecular Mediators Of Valve Mechanobiologysupporting
confidence: 56%
“…The nucleus is the largest organelle in the cell, with a diameter between 3–15 µm [11,12], making it substantially larger than many pores encountered during migration in physiological tissues. Furthermore, biophysical measurements of isolated nuclei and intact cells reveal that the nucleus is typically 2- to 10-times stiffer than the surrounding cytoplasm [11].…”
Section: The Size and Rigidity Of The Nucleus: A Physical Barrier Formentioning
confidence: 99%
“…Furthermore, biophysical measurements of isolated nuclei and intact cells reveal that the nucleus is typically 2- to 10-times stiffer than the surrounding cytoplasm [11]. This combination of large size and relative rigidity of the nucleus led to the hypothesis that the nucleus can impact the cells’ ability to migrate [13].…”
Section: The Size and Rigidity Of The Nucleus: A Physical Barrier Formentioning
confidence: 99%
“…Currently, extracting mechanical properties of the nucleus requires staining, along with additional information and assumptions about how forces are transmitted within a cell. For pristine mechanical information, the nucleus has to be isolated to allow AFM or micropipette measurement, which makes the procedure not suitable for microfluidic platforms 17 .…”
Section: Introductionmentioning
confidence: 99%